Does Foreign Exchange Intervention Volume Matter? - Rasmus Fatum; Yohei Yamamoto (University of Copenhagen, Economic Policy Research Unit (EPRU), 2012)
We investigate whether foreign exchange intervention volume matters for the exchange rate effects of intervention. Our investigation employs daily data on Japanese interventions from April 1991 to April 2012 and time-series estimations, non-temporal threshold analysis, as well as binary choice models. We find that intervention volume matters for the effects of intervention, but only to the extent that the exchange rate effect per intervention unit is magnified in a linear sense by the larger intervention amount. This is a policy-relevant finding that also adds to our understanding of how intervention works.
Keywords: E52; F31; G14; 330; Foreign Exchange Market Intervention; Intervention Volume; Wechselkurspolitik; Wechselkurs; Zeitreihe; Japan